PENGARUH BBLR TERHADAP KEJADIAN STUNTING PADA ANAK USIA 12-60 BULAN DI WILAYAH KERJA PUSKESMAS TANJUNG LANGKAT TAHUN 2017 - Zahriany, Ade Ira (Jurnal Riset Hesti Medan, 2017)
Poor nutrition causes the prevalence of stunting (short children) to be very high, affecting one in three children 12 - 60 months, which is a proportion of public health problems according to the criteria of the World Health Organization (WHO). The Tanjung Langkat Health Center report on infectious diseases suffered by children under five in the Tanjung Langkat Health Center working area, ARI and Diarrhea is quite high among toddlers, namely 17.7% and 29.8%. This research is an analytic research study with case control design, which is an analytic study concerning how risk factors are studied using a retrospective approach. In other words, the effects (illness or health status) are identified at this time, then identified risk factors exist or occurred in the past. The results showed that children aged 12-60 months who had low birth weight and got stunting in the working area of Tanjung Langkat 58 Padang Puskesmas in 2015 were 15 people (48.39%), while normal children who suffered stunting were 16 people (51, 61%). This research is not in line with other studies which say that stunting children have more history of low birth weight. It is expected that Puskesmas Tanjung Langkat health workers will get children born with low birth weight, so health workers provide information that they have a risk of suffering from stunting (short), and are advised to maintain their health and pay attention to their parenting.